2012
DOI: 10.1258/ebm.2011.011193
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of heme oxygenase-1 in human gastric cancer

Abstract: Heme oxygenase-1 (HO-1) potently influences tumor growth and metastasis. To date, no study has been performed on HO-1 expression pattern and its clinicopathological significance in human gastric cancer (GC) cases. In this study, the expression of HO-1 in human GC tissues (n = 74) and matched non-tumoral adjacent parenchyma (n = 46) was investigated by immunohistochemistry. The correlation of HO-1 with the clinicopathological characteristics was analyzed. Results showed that HO-1 was expressed in 62 GC tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 36 publications
(53 reference statements)
9
46
1
Order By: Relevance
“…These findings were consistent with the outcome got from a recent clinical study in gastric cancer patients to some extent, which showed a relatively high expression of HO-1 in human gastric cancer tissues (83.8%), compared to those in adjacent non-tumoral gastric tissues (43.8%) [43]. Accordingly, similar to most previous literatures as described above, upregulation of HO-1 seems to be one of typical biological features of CRC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings were consistent with the outcome got from a recent clinical study in gastric cancer patients to some extent, which showed a relatively high expression of HO-1 in human gastric cancer tissues (83.8%), compared to those in adjacent non-tumoral gastric tissues (43.8%) [43]. Accordingly, similar to most previous literatures as described above, upregulation of HO-1 seems to be one of typical biological features of CRC.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were also found in the recent clinical study of gastric cancers and oral squamous cell carcinomas [21,43]. These results seem to be in contrast to the common notions, namely HO-1 is widely known as a protective molecules in tumor cells against various stress (e.g., oxidative stress from infiltrated leukocytes and macrophages) to support the rapid tumor growth [17,32], thus aggressive and progressing tumors are thought to be accompanied with increased HO-1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to numerous physiological functions, HO-1 has important roles in various pathological conditions, including certain types of cancer. Increased expression levels of HO-1 were previously demonstrated to be associated with malignant potential, cancer cell dissemination and poor prognosis in renal cell, lung and gastric carcinomas (14,25,26). However, other studies have indicated that increased HO-1 expression levels are associated with favorable outcomes in colorectal (27) and tongue cancers (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has important cellular functions in growth regulation and self-defense processes resisting a wide range of external stress stimuli. Overexpression of HO-1 has been found in chemoresistant myeloma ($2-fold) (Nowis et al, 2008), GC ($6-fold) (Yin et al, 2012), lung cancer ($2.5-fold) (Jeon et al, 2012), myeloid leukemia (2-11-fold) (Heasman et al, 2011). Although silenced HO-1 could abrogate drug resistance developed in the treatment with antitumor agents, the detailed mechanisms for HO-1-induced chemoresistance remain unclear.…”
Section: Other Metabolism-related Genes Targeted By Nrf2 In Cancermentioning
confidence: 99%